Perceraian dalam Perspektif Psikologi Pendidikan Islam: Kajian Literatur tentang Dampak, Resiliensi, dan Implikasi Pendidikan Karakter Anak - Melani Ida Marini; Siti Rohimah (Lembaga Yasin AlSys, 2026)
The phenomenon of divorce in Indonesia continues to increase, with more than 463,000 divorce cases decided in 2023, or an increase of approximately 15.3% compared with the previous year, and has caused profound psychological impacts, particularly on children during their developmental period. Although many studies on divorce have been conducted, reviews that specifically integrate the perspective of Islamic educational psychology remain limited. This study aims to analyze divorce from the perspective of Islamic educational psychology, examine its multilayered psychological impacts on children, and identify Islamic value-based resilience strategies relevant to children’s character education. This study used library research with a qualitative-descriptive approach through content analysis of primary and secondary literature sources published between 2012 and 2025. Data were collected from 47 sources obtained through Google Scholar, JSTOR, ERIC, and institutional repositories. The findings show that divorce affects children’s emotional, cognitive, social, and spiritual dimensions. Islamic values, such as patience, tawakkal, and gratitude, serve as sources of resilience in facing these impacts. This study produced five main conceptual findings, namely the Multilayered Impact Model, the Spiritual Resilience Paradox, the centrality of the mother’s role as madrasatul ula, socio-cultural stigma as an obstacle to resilience, and the urgency of developing an integrated Islamic counseling model. These findings contribute to the development of Islamic educational psychology theory and offer a practical framework for educators, counselors, and policymakers in designing psychological support programs grounded in Islamic educational values.